Meningkatkan Motivasi Dan Kreativitas Siswa Menggunakan Model Pandora Pada Kelas IV di SDN Puntik Dalam - Muhammad Maulidi Rahman; Akhmad Riandy Agusta (CV. ITTC INDONESIA, 2023)
The problems that occur in this study are that students have not actively involved themselves, have not worked with friends, this has an impact on student activity in participating in PKN learning to be low. Another problem that arises is that students feel bored and unenthusiastic, this has an impact on students' attention being not focused on learning so that student motivation becomes low. The impact if this problem is not resolved is certainly not developing knowledge and understanding of the concept of PKN, lack of cooperation between students, students are not motivated, lack of curiosity, does not develop creative thinking, students who become passive in learning so that it will certainly affect activities and student learning outcomes decreased. The purpose of this study was to analyze the increase in motivation, activity, creativity, and student learning outcomes after participating in learning using the PANDORA model. This study used a qualitative approach with the type of Classroom Action Research (PTK) which was carried out in four meetings. The research subjects were grade IV even semester students at SDN Puntik Dalam for the 2022-2023 academic year with a total of 23 students. The purpose of this study was to analyze the increase in motivation, activity, creativity and student learning outcomes. The data in this study were obtained through observations of teacher and student activities, student motivation, student creativity, and individual written tests. Data analysis with descriptive analysis techniques presented in tables and graphs is interpreted with the percentages and indicators of completeness of learning outcomes set.